The Impact of the Heritage of Islamic Civilization on Social Development in the Modern Era: Case Studies in Muslim Countries - Syafi'i, Nur Muhammad (Sekolah Tinggi Agama Islam Kuningan, 2024)
The legacy of Islamic civilization holds social and economic values relevant to social development in contemporary Muslim-majority countries. Values such as social justice, collective responsibility, and solidarity have shaped various welfare and economic policies in these regions. This study aims to analyze the impact of applying Islamic values to modern social policies in Muslim countries, focusing on the contributions of zakat, waqf, and Islamic banking in reducing social inequality and enhancing community welfare. A descriptive qualitative method was employed, utilizing a case study approach in several Muslim-majority countries with a strong history of adopting Islamic values in social policies, including Indonesia, Pakistan, and Egypt. Data were gathered through document analysis, expert interviews, and socio-economic statistics from international reports. The findings show that implementing Islamic civilizational values positively impacts welfare distribution, increases access to education, and promotes economic stability within communities. This study highlights the importance of utilizing Islamic values in shaping sustainable social development policies in the modern era.